Attentional Problems Occur Across Multiple Psychiatric Disorders and Are Not Specific for ADHD - Grant, Jon E. (CNS Spectr, 2023)
OBJECTIVE: Attentional problems are common and have been associated with multiple psychiatric disorders. This study examined problems of sustained attention across a range of psychiatric disorders using a validated computerized trans-diagnostic attentional paradigm (a Continuous Performance Task). We hypothesized that multiple psychiatric disorders, particularly ADHD, would be associated with pronounced attentional problems in young adults versus controls. METHODS: 576 non-treatment seeking participants (aged 18-29 years) were enrolled from general community settings, and provided information regarding demographic variables and underwent clinical assessments to detect a range of mental health disorders. Each participant underwent the Rapid Visual Information Processing (RVP) task, a previously validated computerized test measuring sustained attention. The two measures of sustained attention were the sensitivity index, and target detection (proportion of targets detected). The profile of attentional deficits was examined across different disorders using z-scores relative to controls. RESULTS: Participants with social phobia, OCD, bulimia nervosa, and intermittent explosive disorder showed the greater impairment in target sensitivity, all with effect sizes of at least 0.8. Target detection was impaired across multiple disorders, with OCD and binge eating disorder exhibiting the most pronounced impairment. PTSD and compulsive sexual behavior were associated with particularly spared performance on both measures. DISCUSSION: These data indicate that impaired attention is non-specific for ADHD and in fact several other disorders are associated with markedly larger deficits. Instead of clinicians assuming sustained attention problems are due to ADHD, a variety of disorders should be screened for when people report attentional problems. Future work should examine the contribution of comorbidities and psychoactive substances (prescribed or illicit) to the profiles identified.